Older adults’ experiences of team-based home rehabilitation–a qualitative scoping review - Johansson, Anette; Torgé, Cristina Joy; Baudin, Katarina; Fristedt, Sofi; Rydwik, Elisabeth; Ernsth Bravell, Marie (Disability and Rehabilitation, 2025)
Purpose: To map and summarise the available knowledge regarding older adults’ experiences of team-based home rehabilitation. Method: The Johanna Briggs Institute (JBI) guidelines for scoping reviews guided the process. Eight databases, eight organisational websites, one registry and Google Scholar were searched. Searches were limited to publications published from 2006 to 2023 in English and Scandinavian languages. Data were extracted from the eligible publications using a data extracting tool developed for this study. Extracted data were condensed and coded into categories. Results: Seventeen publications, conducted mainly in Scandinavian countries, were included. Older adults’ experiences of team-based home rehabilitation were identified and categorised as: home as a rehabilitation context; staff′s attitudes, approach and collaboration; the intervention process, content and outcome; and impact of the older adults’ own personal conditions. Conclusions: This scoping review provides insight into older adults’ experiences of team-based home rehabilitation. Although the majority were positive towards receiving rehabilitation in their homes there were also negative experiences that need to be further explored. An identified knowledge gap in team-based home rehabilitation research is the lack of cultural aspects. Moreover, there is a need of consensus among researchers on how to report on population, context and content in team-based home rehabilitation.
Keywords: ADL; independent living; occupational therapist; person-centred; physiotherapist; rehabilitation context; stay-in-place